Effect of preoperative intravenous steroids on seroma formation after modified radical mastectomy - Uzma Shamim Seth; Sughra Perveen; Imran Khan; Tanwer Ahmed; Muhammad Taha Kamal; Munira Murtaza Khomusi (Journal of the Pakistan Medical Association, 2022)
Objective: To analyse the efficacy of preoperative intravenous injection of 120mg of methylprednisolone acetate steroid on the formation of seroma after modified radical mastectomy in breast cancer patients. Method: The case-control study was conducted at Ward 3, Surgical Unit 1, Department of General Surgery, Jinnah Postgraduate Medical Centre, Karachi, from November 2020 to April 2021, and comprised female patients with biopsy-proven carcinoma of breast who were scheduled for elective definitive breast cancer surgery. The subjects were randomised into treatment group A and control group B. Group A was given a single dose of intravenous injection methylprednisolone acetate 120mg half-an-hour before surgery, while group B underwent similar surgery without the said injection. Seroma was graded using the Common Terminology Criteria for Adverse Events v3.0. The groups were compared for age, total drainage, duration of drainage, seroma grading and wound status. Data was analysed using SPSS 25. Results: Of the 60 patients, there were 30(50%) in each of the two groups. The age difference between groups was non-significant (p=0.346). There was a significant difference in the mean total drainage volume and mean duration of drainage between the groups (p=0.001). Seroma formation, seroma grading and wound status were not significantly different between the groups (p>0.05). The efficacy in treatment was high in group A (odds ratio: 2.78; 95% confidence interval: 0.65-13.94). Conclusion: A single preoperative dose of Injection methylprednisolone acetate was effective in terms of post-mastectomy outcomes. Key Words: Modified radical mastectomy, Methylprednisolone, Formation of seroma.